Finale furioso: referee-biased injury times and their effects on home advantage in football - Riedl, D.; Strauss, B.; Heuer, A.; Rubner, O. (Journal of Sports Sciences, 2015)
The role of referees has become a central issue in the investigation of home advantage. The main aim of this study was a thorough examination of the referee bias concerning injury time in football, which is currently seen as an important example for the assertion that referees contribute to home advantage. First, we use archival data from the German Bundesliga (seasons 2000/2001-2010/2011) to confirm the existence of an asymmetry in the allocation of injury time. We show this asymmetry to be a bias by ruling out hitherto remaining alternative explanations (effect = 18 s, P < 0.001, = 0.05). Second, we identify a further referee bias, stating that referees systematically accord more injury time when one team leads in the game compared to a draw (effect = 21 s, P = 0.004, = 0.06). Third, the quantitative benefit of home or away teams in goals and points due to these biases is assessed. Overall, referee decisions on injury time indeed reveal biases, but they do not contribute to the home advantage, that is, there is no significant effect on goals scored by the teams. The qualitative findings (a new bias on injury time) as well as the quantitative findings (no overall effect) shed new light on the role of referees for home advantage.